Determination of the interaction between a masonry wall and a confining frame. (15th July 2018) - Brodsky, Alex; Rabinovitch, Oded; Yankelevsky, David Z.
Highlights: Interaction between a masonry wall and a frame is experimentally investigated. An innovative experimental facility enables to identify contact zones. The instrumented testing frame provides data on the contact zone tractions. Different contact zones are developed in monotonic and cyclic loadings tests. The new data contributes new important data on the complex interaction. Abstract: This paper studies the interaction between an infill masonry wall and its surrounding frame. The investigation is motivated by the lack of experimental data on the interaction regarding the contacted and detached areas between the wall and the frame and the interaction tractions at the contact regions. It is important to note that the interaction between the masonry wall and the surrounding frame plays a critical role in the frame response as it governs the shear and bending moment resultants along the frame elements. It is more critical in the case of strong infill walls surrounded by a relatively weak frame and it may lead to premature failure of the frame at an early stage of loading and affect the overall resistance of the wall-frame system. Such observations were obtained in numerous tests on masonry infilled frames subjected to lateral loading to simulate earthquake loading and in a limited number of tests on masonry infilled frames subjected to a vertical load simulating the case of loss of a supporting column. This paper investigates the interaction behaviour in terms of the infill-frame contact regions and interfacial tractions in such event of loss of a supporting column. In this scenario, the interactive action becomes critical to the structure's safety against the possible development of progressive collapse. This scenario has gained considerably less attention compared with the behaviour of this system to lateral loading. The main goal of this study is to shed light on the frame-infill wall interaction with focus on the contact zones and the contact pressures between an infill wall and a confining frame. The paper presents a new experimental methodology that follows the interaction between the frame and the infill wall along their common interfaces in order to detect the contact regions and the interaction stresses along these areas as well as their evolution and change during a loading process. The effect of monotonic and cyclic loading patterns on cracking of the infill wall and its impact on the contact regions with the frame and the interfacial tractions are also investigated. The experimental results of this study can support the development of new models that consider the infill-frame interaction and its impact on the structural response.